Penafsiran Hakim Pengadilan Agama Terhadap Ketentuan Hak Waris Saudara Dalam Kompilasi Hukum Islam Di DIY - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Basically, the provision of relative's inheritance rights has been regulated on Holy Quran in the Chapter of An Nisaa : 12 and 176. However, the distinction of interpreting the walad and kalalah pronuciation of this Chapter has resulted in the differences of defining the relative's inheritance rights. There are two main different teachings concerning relative's inheritance rights under the Islamic Law, namely ahlussunnah with its paternalistic line system and Hazairin teaching with its bilateral style. The Compilation of Islamic Law exists as a material law in Religion Court adopting none of the two teachings. The research is aimed to describe the interpretation of the judges at Religion Court in Yogyakarta Special Province on relative inheritance rights provision in the Compilation of Islamic Law, as expressed in the articles 181 and 182 of KHI. The data were obtained from interview with the judges at Religion Court in Yogyakarta Special Province, accompanied by documentary studies on secondary data. The research shows, the judges rule that relatives will never inherit anything when the inheritor has children, whether sons or daughters and he/she has a father